Flexural behavior of irregular flat floors - Koh, Tee Rong. (2009)
The use of flat plate has offered building professionals many advantages over other slab systems. Often, architects design irregular flat plate system to meet the increasing demands of the end-user. As structural engineers had to arrange reinforcements to be slant with respect to the global axis and no existing engineering code is able to fulfil its structural needs, they had to over-reinforce the slab due to the lacking of understanding of the behaviour of such slabs. The aims of this report were to investigate the flexural behaviour of irregular flat plate structure with irregular column layout analytically and to determine approach(s) to convert the global bending moments. A total of 14 slabs were simulated analytically through the use of finite element analysis. Results were compared using two approaches to determine the moments against the moment capacities. A method, based on finite element method, was also proposed for the design of irregular flat plate structures.